PERUBAHAN PENYELENGGARAAN PESTA PERKAWINAN DAN PUDARNYA SOLIDARITAS SOSIAL MASYARAKAT PEDESAAN: STUDI KASUS DI KABUPATEN SOLOK - Fitri, Rahmiatil; Elfitra, Elfitra; Maihasni, Maihasni (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This article will discuss the link between social change and social solidarity. The discussion will focus on the form of social changes on marriage ceremony on social solidarity within Minangkabau rural communities. Based on a study in a nagari in Solok district in West Sumatra this article will convey the form of marriage ceremony changes that occurred in the nagari and consequently to the sustainability of the mechanism of maintaining the solidarity of relatives in the nagari community. It will be shown that the marriage ceremony changed from previously fully organized by relatives working together from preparing facilities to serving food and drink, and decorate the party location into the use of Wedding Service services that took over the preparation of party facilities, decorate the party location, and bridal makeup. This change is welcomed by the community, but the presence of Wedding ServiceÂ has reduced the involvement of kin members in the preparation and holding of a marriage feast and this then disrupts the mechanism of social solidarity sustainability within the kinship group.